2015
DOI: 10.1378/chest.14-0692
|View full text |Cite
|
Sign up to set email alerts
|

Preintubation Application of Oral Chlorhexidine Does Not Provide Additional Benefit in Prevention of Early-Onset Ventilator-Associated Pneumonia

Abstract: BACKGROUND: Daily application of oral chlorhexidine gluconate (CHX) following intubation to reduce the risk of ventilator-associated pneumonia (VAP) is now the standard of care in many ICUs. Th is randomized clinical trial evaluated the benefi t of adding a preintubation CHX dose to the known benefi t of postintubation CHX to reduce the risk of early-onset VAP. A secondary aim was to test the effect of a preintubation oral application of CHX on early endotracheal tube (ETT) colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
(12 reference statements)
2
13
0
Order By: Relevance
“…Munro et al traced the effect of their intervention for 14 days and reported that CHX was effective in preventing VAP infections only up to the 3rd day (26). In the current study, it was observed that CHX had the same effect as ozonated water on the prevention of VAP infections up to the 3rd day.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Munro et al traced the effect of their intervention for 14 days and reported that CHX was effective in preventing VAP infections only up to the 3rd day (26). In the current study, it was observed that CHX had the same effect as ozonated water on the prevention of VAP infections up to the 3rd day.…”
Section: Discussionsupporting
confidence: 61%
“…Some studies found that CHX was ineffective to prevent VAP infection (13,26). Munro et al traced the effect of their intervention for 14 days and reported that CHX was effective in preventing VAP infections only up to the 3rd day (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant benefit on mortality, days of mechanical ventilation or length of ICU stay. A recent RCT by Munro et al used chlorhexidine prior to intubation to determine if this would decrease the rates of VAP compared to patients who were not pre-treated with chlorhexidine before being intubated [57]. All patients subsequently received chlorhexidine twice daily.…”
Section: Non-invasive Positive Pressure Ventilation (Nippv)mentioning
confidence: 99%
“…This study is the third clinical trial to test early administration of oral chlorhexidine to reduce the risk of VAP [25,26] but the first to apply chlorhexidine in the prehospital environment for a very high risk cohort [11]. Considering these trials in aggregate, the only observed difference in clinical outcome was reported in a single trial that attributed efficacy to imbalances in baseline risk for pneumonia-there was not actually a raw difference observed in the primary end point 48 or 72 hours after admission [26].…”
Section: Discussionmentioning
confidence: 99%